Analysis of the chromatic characteristics, on land cover types using synthetic aperture images - Auccahuasi, W. (2020)
When it is required to study the terrestrial coverage in large dimensions, the use of remote sensors is used, these provide us with information according to the type and coverage that they present in their configuration, these remote sensors present in general two types of images in accordance To the instrument they have on board, we first have the optical sensors that are on board the observation satellites, which provide information of the terrestrial coverage based on a representation of pixels that make up an image, they are characterized by the bands of colors Red, Green, Blue and in other bands such as short wave infrared and medium wave infrared among others that may have according to their purpose, these images present a level of detail according to their special resolution that can be metric and sub metric, one of the disadvantages of these sensors is that in the presence of cloud cover the image that generates is the image of the clouds, so you can not make a good acquisition when you have the presence of clouds, before this problem we have the other group of remote sensors that work by using electromagnetic waves which is emitted from the satellite in space and measures the rebound that exerts on the earth, generating an image, this image has a feature that does not present a level of detail compared to optical images, its image is a representation in texture form of the surface to which the emitted signal made the rebound, this type of satellites are called satellite synthetic aperture, or radar satellite (SAR), one of its advantages that has and that makes it useful, is that in the presence of cloud cover, the satellite will have The signal reflected in the earth can therefore be made an acquisition of the area of ​​interest even if there is cloud cover and can be acquired independent of the time, so it can be at night as in the day, the image produced is a 16-bit grayscale image, in the present research work will be made the analysis of certain areas of land cover presented in the Peruvian jungle as, vegetation, area contaminated by illegal mining and mountain.